Two Greek painters’ signatures - Parpulov Georgi (Zograf)
I publish two neglected painters’ signatures found in illustrated Greek manuscripts. By coincidence, both accompany an image of the evangelist John preceding the text of his gospel, and the respective codices are both kept in German libraries, in Wolfenbuttel and in Gotha. In one case, the words χηρ νικιτα (“hand of Nicetas”) are written below John’s image in large capitals. The image is datable on stylistic grounds to ca. 1300. Its painter is otherwise unattested, but the unusually prominent placing of his name is worthy of note. The second signature is less prominent but even more curious, for it reads Δομήνικος Κρής, i.e. “Dominic, a Cretan”. This is none other than the famous El Greco. The miniature’s style is comparable to works from his Venetian period (1567-1570).